Simple Preparation of New Potential Bioactive Nitrogen-Containing Molecules and Their Spectroscopy Analysis - Kouznetsov, Vladimir V.; Galvis, Carlos E. Puerto; Méndez, Leonor Y. Vargas; Gómez, Carlos M. Meléndez (IntechOpen, 2012)
None